Kształtowanie się zasięgu stref zalewowych w następstwie obniżeń powierzchni terenu wywołanych prognozowaną eksploatacją węgla kamiennego = Shaping of the floodplain boundaries following the land area slump caused by the forecasted coal mining exploitation - Czajkowska, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the upper part of the basin of Kłodnica river hydrographic conditions are shaped primarily by decades of mining activity, which contributes to the formation of flooding and fens in the river valley and its tributaries.
Keywords: strefa zalewowa; osiadanie powierzchni terenu; tereny górnicze; węgiel kamienny; eksploatacja węgla kamiennego; oprogramowanie MIKE FLOOD; floodplains; land subsidence; mining areas; coal mining exploitation; MIKE FLOOD software